IMPLEMENTASI PROGRAM REHABILITASI SOSIAL ANAK YANG BERHADAPAN DENGAN HUKUM (ABH) DI DINAS SOSIAL KABUPATEN LAMONGAN - Adelia Meitasari; Badrudin Kurniawan (Publika, 2022)
The existence of children is closely related to the continuation of a life process, there are problems that befall children so that there is a need for legal protection of children. The Lamongan Regency Government has an effort to protect children's rights with the ABH Social Rehabilitation Program which is handled by the Lamongan Regency Social Service. The formulation of the research problem is how to implement the ABH Social Rehabilitation Program, using descriptive research with qualitative research methods. Data collection techniques were obtained through interviews, observations, and documentation at the Lamongan District Social Service. The results of this study, firstly, the standards and policy objectives are in accordance with the regulations and procedures, namely the Criminal Investigation Department and the Ministerial Regulation, only that they do not have an official SOP made by the Lamongan District Social Service. Second, financial and human resources have met the need for the ongoing ABH Social Rehabilitation Program. Third, communication between organizations that are established with several government agencies and private organizations is well established through coordination meetings, meetings, and communication through social media. Fourth, the characteristics of the implementing agency, namely the Social Service of Lamongan Regency, have a disciplined character and are responsible for the ABH Social Rehabilitation Program. Fifth, there is support for ABH from government agencies, private organizations, and companies in providing support in the form of monetary donations, training, and places for ABH Social Rehabilitation. Sixth, the disposition of the implementers has applied their understanding and abilities to the tasks carried out by providing good service responses to ABH. The conclusion is that the implementation of the ABH Social Rehabilitation Program at the Lamongan District Social Service has fulfilled 5 of the 6 theoretical variables of Donald S. Van Meter and Carl E. Van Horn. Keywords: Implementation, Social Rehabilitation, Children in Conflict with the Law (ABH)